2020
DOI: 10.1016/j.jtbi.2020.110331
|View full text |Cite
|
Sign up to set email alerts
|

Aging a little: On the optimality of limited senescence in Escherichia coli

Abstract: Recent studies have shown that even in the absence of extrinsic stress, the morphologically symmetrically dividing model bacteria Escherichia coli do not generate offspring with equal reproductive fitness. Instead, daughter cells exhibit asymmetric division times that converge to two distinct growth states. This represents a limited senescence / rejuvenation process derived from asymmetric division that is stable for hundreds of generations. It remains unclear why the bacteria do not continue the senescence be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Considering most assumptions of these models, extreme damage segregation might not lead to maximum population growth rates, that is, perfect symmetry or complete asymmetry appears to be only favored under simplistic assumptions. Model predictions range between complete asymmetry, intermediate asymmetry, or no asymmetry (Watve et al, 2006;Ackermann et al, 2007;Evans and Steinsaltz, 2007;Erjavec et al, 2008;Chao, 2010;Rashidi et al, 2012;Clegg et al, 2014;Moger-Reischer and Lennon, 2019;Blitvić and Fernandez, 2020). This implies for populations segregating the accumulating damage in an optimal asymmetric fashion, whose lines of descendants that continuously inherit the larger fraction of damage go extinct after some variable time, while the population-consisting of many lines, including those that inherit small fractions of damage-remains viable.…”
Section: Asymmetry In Damage Distribution and Senescencementioning
confidence: 99%
See 2 more Smart Citations
“…Considering most assumptions of these models, extreme damage segregation might not lead to maximum population growth rates, that is, perfect symmetry or complete asymmetry appears to be only favored under simplistic assumptions. Model predictions range between complete asymmetry, intermediate asymmetry, or no asymmetry (Watve et al, 2006;Ackermann et al, 2007;Evans and Steinsaltz, 2007;Erjavec et al, 2008;Chao, 2010;Rashidi et al, 2012;Clegg et al, 2014;Moger-Reischer and Lennon, 2019;Blitvić and Fernandez, 2020). This implies for populations segregating the accumulating damage in an optimal asymmetric fashion, whose lines of descendants that continuously inherit the larger fraction of damage go extinct after some variable time, while the population-consisting of many lines, including those that inherit small fractions of damage-remains viable.…”
Section: Asymmetry In Damage Distribution and Senescencementioning
confidence: 99%
“…Also, under such assumptions, the growth rate (fitness) of the two types of lineages is not equal since faster dividing lineages will grow faster and therefore contribute to larger fractions to the overall population. This fitness difference due to differences in generation times results in non-stable equilibria at the population level, though at the single-cell lineage level, equilibria might be observed (Blitvić and Fernandez, 2020). The model predicting two growth equilibria is supported by empirical data under benign conditions where no senescence, with respect to cell growth, has been observed (Proenca et al, 2018(Proenca et al, , 2019, though other studies performed under conditions that mirrored largely the study conditions of Proenca et al (2019) revealed senescence by illustrating declining growth rates (or increased doubling times) with age (Łapińska et al, 2019).…”
Section: Asymmetry In Damage Distribution and Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…In the next section, we apply the self-consistent Equation 10 to a toy model of E. coli recently published by Blitvic et al [13] as a simple example.…”
Section: Transport Equationmentioning
confidence: 99%
“…A number of computational and theoretical studies addressed the dynamics of asymmetric damage segregation (ADS) in a growing microbial population and their implications for the overall population fitness [7][8][9][10][11][12][13][14][15]. In [9,11] it was demonstrated numerically that asymmetry accelerates the average growth of the population as a whole.…”
Section: Introductionmentioning
confidence: 99%